Influence of hydro, mechanical, and chemical treatments to seed for germination and seedling growth of Saraca asoca (Roxb. de Wilde) - Manohar Kandileri, Abha; Shukla, Gopal; Louis, Libin T.; Kizha, Anil Raj; Husen, Azamal; Chakravarty, Sumit (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
It has been noticed that Saraca asoca (Roxb. de Wilde) populations are drastically declining in the wild. Conserving such populations is crucial because of the numerous ecological, cultural, and economic values. The purpose of our study was to determine if germination and seedling growth could be improved for globally vulnerable Ashoka populations. The study analyzed the effect of various hydro, mechanical, and chemical pre-sowing treatments on the germination and one-year growth of Ashoka seedlings. Our results demonstrated that mechanical (exposing the seed cotyledons) and soaking of seeds in hot water treatments (60 °C) were better than all other water- and chemical-based pre-sowing treatments used in the study of enhancing germination. Nevertheless, chemical treatments were better for the growth and survival of the seedlings. This methodology offers to restore the scattered populations of Ashoka that are facing the risk of extinction in the wild while successfully meeting the commercial demand for this medicinal tree.